2021
DOI: 10.3390/insects12010082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deformed Wing Virus Infection on Expressions of Immune- and Apoptosis-Related Genes in Western Honeybees (Apis mellifera)

Abstract: Honeybees are globally threatened by several pathogens, especially deformed wing virus (DWV), as the presence of DWV in western honeybees is indicative of colony loss. The high mortality rate is further exacerbated by the lack of effective treatment, and therefore understanding the immune and apoptosis responses could pave an avenue for the treatment method. In this study, DWV was directly injected into the white-eyed pupae stage of western honeybees (Apis mellifera). The DWV loads and selected gene responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…Viral infection within the host via viral entry, replication, and spreading can induce the antiviral innate immune responses [ 66 ]. Upregulation of several AMP genes, including abaecin , hymenoptaecin , and defensin , was also shown in other studies where honey bees were infected with DWV-A [ 56 ]. Treatment with thiamethoxam led to the downregulation of abaecin and defensin genes in crippled wings adult honey bees.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Viral infection within the host via viral entry, replication, and spreading can induce the antiviral innate immune responses [ 66 ]. Upregulation of several AMP genes, including abaecin , hymenoptaecin , and defensin , was also shown in other studies where honey bees were infected with DWV-A [ 56 ]. Treatment with thiamethoxam led to the downregulation of abaecin and defensin genes in crippled wings adult honey bees.…”
Section: Discussionsupporting
confidence: 67%
“…Our study demonstrated that the effects of treatment with only thiamethoxam induce increased wing deformity in newly emerged adult honey bees. Moreover, numerous studies have also demonstrated that DWV is also the cause of crippled wings in honey bees [ 56 , 59 ]. Our result showed that honey bees exposed to thiamethoxam and DWV-A stressors had a high percentage of crippled wings as newly emerged adult honey bees.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations